Volcanic hazard knowledge and preparedness of small island community on the flank of Gamalama volcano Ternate Island–Indonesia - Hidayat, Agung (Springer Science and Business Media Deutschland GmbH, 2023)
A study of volcanic hazard knowledge and preparedness of communities living on the flanks of Gamalama Volcano, on the small island Ternate, was conducted in January–February 2019. A total of 1265 respondents participated in a questionnaire-based survey using 42 questions to inquire about community knowledge of natural disasters and volcanic hazards, community preparedness, and the correlation between community knowledge and preparedness. The results showed that the majority of respondents selected from the small island community had good knowledge of natural disasters and volcanic hazards and were also well-prepared. There are positive correlations between knowledge of natural disasters and volcanic hazards; the latter is also positively linked to preparedness. Long experience in dealing with the eruptions of Gamalama in the past has raised local people’s awareness of volcanic hazards, which in turn increases their preparedness. Such understanding and preparedness are inseparable from the abundant dissemination channels of details on eruption threats and risks on Ternate Island, including televisions, the internet, radios, government officials, and non-governmental organizations. © 2022, The Author(s), under exclusive licence to Springer Nature B.V.